Frieden durch Kommunikation. Das System Genscher und die Entspannungspolitik im Zweiten Kalten Krieg 1979-1982/83 - Bresselau von Bressensdorf, Agnes (Studien zur Zeitgeschichte, 2015)
At the end of the 1970s West Germany`s foreign minister Genscher faced the challenge of defending the Social-Liberal coalition`s policy of dètente against the approaching Second Cold War.&#8206 The unique features of his communication policy were demonstrated in his responses to the Soviet invasion of Afghanistan and the Polish crisis. The author sees the basis for his long-term success as stemming from a specific Genscher system.